Effect of different water supply on the growth of kiwiberry vine cultivated in substrate - LI Hao; SUN Xiaoxu; QI Xiujuan; GU Hong; LI Lan; CHENG Dawei; CHEN Jinyong; YANG Yingjun (Guoshu xuebao)
[Objective] This study aimed to investigate the effects of different levels of irrigation on the growth dynamics of Zhong Hong Bei 7 hao kiwiberry (Actinidia arguta) vine under substrate cultivation. The primary goal was to identify the most suitable water management strategy to enhance the growth performance of the kiwiberry. By evaluating various irrigation strategies, the study sought to provide scientific recommendations and practical guidelines for optimizing substrate cultivation of kiwiberry. [Methods] One-year-old kiwiberry plants were selected for the experiment. On March 12, 2023, the kiwiberry plants grown from nursery bags were transplanted into a rain-shelter, using cylindrical nutrient bags with a diameter of 60 cm and a height of 60 cm for substrate cultivation. The planting density was 2 m × 3 m, and the plants were trained into a single main trunk with two lateral vines in a pinnate shape. The plants were subjected to seven irrigation treatments based on substrate maximum water holding capacity (saturated moisture content, SMC): 60%, 70%, 80%, 90%, 100%, 110%, and 120%. Each treatment was replicated three times to ensure statistical validity. The survival rates were recorded after planting, and growth metrics such as the length and thickness of the main trunk, primary vine, and fruiting branches, as well as leaves size, were measured 84 days after planting. The total net growth and growth increments between measurement intervals were compared across different treatments to assess the impact of irrigation levels on kiwifruit growth. The data analysis was conducted using One way ANOVA and LSD multiple comparison methods to determine the significant effects of different irrigation treatments on growth parameters. [Results] The substrate moisture levels significantly affected the growth performance of kiwiberry. The net growth of the main trunk and primary vine increased significantly with higher substrate moisture levels (p<0.05). Among the treatments, SMC-100%, SMC-110%, and SMC-120% significantly increased the net growth of the main stem's diameter (p<0.01). The SMC-110% treatment yielded the best results. The net growth in the diameter of the main stem and primary vine showed significant increases during T2 (mid to late June), T4 (late July to mid-August), and T5 (late August to mid-September). The net growth in length of the fruiting branches showed a trend of initially increasing and then decreasing with the increase of substrate moisture levels. No significant differences were observed between the SMC-60% and SMC-120% treatments, indicating that the impact of irrigation levels on the length growth of the fruiting vine was quite complex. In contrast, the net growth in thickness of the fruiting vine increased significantly with the higher substrate moisture levels, with notable differences between the low irrigation treatments (e.g., SMC-60%, SMC-70%, SMC-80%) and sufficient irrigation treatments (e.g., SMC-100%, SMC-110%, SMC-120%) (p<0.05). The net growth in the diameter of the fruiting branch showed significant increase during T3 (early July) and T4 (July to mid-August). Regarding the leaf growth indicators, the lower irrigation treatments (e.g., SMC-60%, SMC-70%, SMC-80%) resulted in better leaf performance compared with the higher irrigation treatments (e.g., SMC-100%, SMC-110%, SMC-120%). The periods T2 and T6 were identified as phases of rapid growth for the leaves. The SPAD values and nitrogen content of the leaves were also affected to varying degrees by different substrate moisture levels. Within the same treatment, the trends in the leaf SPAD values and nitrogen content were generally consistent. Notably, leaves under low moisture treatments showed a more rapid response in changes to the SPAD values and nitrogen content. [Conclusion] The different irrigation levels had a significant impact on the growth of kiwiberry. SMC-110% and SMC-120% irrigation levels had biggest effect on the net growth compared with other treatments. SMC-110% or SMC-120% irrigation levels should be adopted as water management strategies in practical cultivation to optimize the growth of kiwiberry.